Ventilator sharing moves forward. Issue 9 (September 2020) - Unknown
Abstract : A ventilator sharing device for Covid-19 patients is being tested by the University of Cambridge's Institute for Manufacturing engineers and anaesthetists from the Royal Papworth Hospital. The device makes it possible to split the airflow from one ventilator, allowing two patients to receive tailored respiratory support.